Implementasi Fatwa DSN-MUI No 07∕DSN MUi∕IV∕2000 pada Akad Mudharabah di BMT X Kecamatan Lembang Kabupaten Bandung Barat - Ilyassa Anzani Sopiani (UNISBA Press, 2024)
Abstract. Sharia banking in Indonesia is experiencing rapid development in the banking world, but existing financial institutions basically only pay attention to certain groups with large projects so that people face various obstacles to accessing capital, so there is often an awareness of self-help and The increasing determination to create an economic system that is fairer, cleaner and in accordance with sharia, then at the beginning of the nineties sharia financial institutions emerged that prioritized services to small communities, namely Baitul Maal Wat Tamwil (BMT), one of the institutions that was seen as being able to provide a solution to this problem. The problem faced by the micro businesses above is the Sharia Savings and Loans and Financing Cooperative BMT Al - Maslahah District, West Bandung, through mudharabah product loans. The problem that will be studied in this research is how mudharabah financing is implemented and how the development of Pasar Lembang MSMEs after getting mudharabah financing at BMT Al - Maslahah District, West Bandung. The aim of this research is to find out and analyze the implementation of mudharabah financing and the development of MSMEs after getting mudharabah financing . because this institution is a community economic institution that is oriented towards helping micro businesses in developing their businesses. The implementation of the Fatwa on MSMEs at BMT has been carried out appropriately, but there is one part that is not appropriate. Abstrak. Perbankan syariah di indonesia sedang mengalami perkembangan didunia perbankan secara pesat, namun lembaga keuangan yang ada pada dasarnya hanya memperhatikan kalangan tertentu dengan proyek-proyek besarnya sehingga masyarakat menghadapi berbagai kendala untuk mengakses permodalan, maka seringnya muncul kesadaran untuk menolong diri sendiri (self help) dan meningkatnya tekad menciptakan sistem ekonomi yang lebih adil, bersih dan sesuai syariah, maka pada awal dekade sembilan puluh muncul lembaga -lembaga keuangan syariah yang mengutamakan pelayanan kepada masyarakat kecil yaitu Baitul Maal Wat Tamwil (BMT) salah satu lembaga yang di pandang dapat memberikan solusi terhadap permasalahan yang dihadapi usaha mikro diatas adalah koperasi Simpan Pinjam dan Pembiayaan Syariah BMT Al – Maslahah Kab, Bandung Barat, melalui pinjaman produk mudharabah. Permasalahan yang akan dikaji dalam penelitian ini adalah bagaimana penerapan pembiayaan mudharabah serta bagaimana perkembangan UMKM Pasar Lembang setelah mendapatkan pembiayaan mudharabah di BMT Al – Maslahah Kab, Bandung Barat, Tujuan penelitian ini adalah ingin mengetahui serta menganalisis penerapan pembiayaan mudharabah dan perkembangan UMKM setelah mendapatkan pembiayaan mudharabah. karena lembaga ini merupakan Lembaga perekonomian umat yang berorientasi membantu usaha mikro dalam mengembangkan usahannya yang mana penerapan Fatwa pada UMKM di BMT sudah melakukan sesuai, tetapida satu bagaian yang tidak sesuai.